Inherited Haemoglobin Disorders Among Apparently Healthy Individuals- An Analysis of 105 Cases (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Inherited hemoglobin disorders present a significant health problem all over the world. Due to migration, this problem is increasing day by day. No definitive data regarding the frequency of hereditary haemoglobin disorders are available in Bangladesh. Iron deficiency is most widely prevalent in the country and beta thalassaemia is also common.Objective: The aim of the study is to determine the relative frequency of inherited haemoglobin disorders among apparently healthy individuals in two different institutes.Methods: This observational cross-sectional prospective study was carried out in the Department of Haematology of Dhaka Medical College Hospital (DMCH), Dhaka for a period of one year from January 2010 to December 2010. Apparently healthy physicians, staffs and students of Dhaka Medical College (DMC) as well as students of Dhaka University (DU) between 18 to 35 years age irrespective of sex were included in the study. Blood samples of specific amount were taken from all these individuals for estimation of CBC, red cell variables and Hb electrophoresis.Results: A total number of 105 respondents were enrolled in this study with the mean age of 25.2 years and female (52.2%) predominance. Hb electrophoresis revealed normal Hb pattern in 89.4% individuals, HbE trait in 4.8%, beta thalassaemia trait in 3.8%. One each of Hereditary Persistence of Fetal Haemoglobin (HPFH) and heterozygous Hb-D Punjab were detected constituting 2.0%. In this present study, a total of 10.6% abnormal Hb pattern was detected.Conclusion: The finding of abnormal Hb pattern on Hb electrophoresis in this study among apparently healthy individuals indicates the high frequency of inherited haemoglobin disorders especially HbE and beta thalassaemia trait in Bangladesh which warrants detection of these disorders and subsequent appropriate genetic counseling.Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014